Bogor Traditional Food Project Module Builds Students’ Competence and Global Character: Modul Proyek Makanan Tradisional Bogor Membangun Kompetensi dan Karakter Global Siswa - Hidayatulloh, Muhamad Syarif; Patras, Yuyun Elisabeth; Arifin, M.Zainal (Academia Open, 2025)
General Background: In an increasingly globalized society, fostering multicultural competence and global diversity character in primary education is critical for shaping tolerant and inclusive citizens. Specific Background: However, educational institutions often lack contextual, engaging materials to cultivate these competencies effectively, particularly through culturally rooted experiences. Knowledge Gap: Despite the potential of local culture as a medium for learning, studies rarely examine its integration through structured project-based modules in primary education. Aims: This study aims to evaluate the effectiveness of a project-based learning module focused on traditional Bogor food in enhancing students’ multicultural competence and global diversity character within the Pancasila Student Profile (P5) framework. Results: Using a quasi-experimental design, the experimental class achieved a high average N-Gain score (0.74) for multicultural competence, surpassing the control class (0.60), and outperformed the control group by 7.5% in global diversity character scores. Novelty: The study introduces a novel instructional strategy that integrates traditional culinary practices into project learning to develop cultural awareness, empathy, and adaptability among elementary students. Implications: These findings suggest that embedding local cultural elements in project-based learning modules is a promising pedagogical approach to enrich multicultural and global character education in primary schools. Highlight : The traditional food project effectively improves students' multicultural competence and global diversity character. Learning through local food enhances cultural understanding, empathy, and inclusive attitudes. The experimental class showed significantly higher N-Gain and global diversity scores than the control group. Keywords : P5 Project Module, Traditional Food, Multicultural Competence, Global Diversity, Primary Education